Breaking the symmetry: Gradient in NiFe layered double hydroxide nanoarrays for efficient oxygen evolution. (June 2019) - Zhou, Daojin; Jia, Yin; Duan, Xinxuan; Tang, Jialun; Xu, Jie; Liu, Dong; Xiong, Xuya; Zhang, Junming; Luo, Jun; Zheng, Lirong; Liu, Bin; Kuang, Yun; et al.
Abstract: Breaking the symmetry in catalysts through interface engineering has emerged as a new dimension in enhancing the catalytic performances, while the long-range asymmetry (i.e. in nanometer scale) in catalysts can hardly be achieved by alloying or doping. Herein, we introduce asymmetrical gradient effect into NiFe layered double hydroxide (NiFe-LDH) at nano scale via a simple nanoarray construction strategy on Ni foam substrate. The electron energy loss spectroscopy, extended X-Ray absorption fine structure and other characterizations together revealed the concentration and valence states gradients in NiFe-LDH nanoarrays. Subsequently, the gradient effect leads to distinctly optimized binding strength of active sites to oxygen evolution intermediates, better electron transfers and boosted oxygen evolution performances, which are absent in non-gradient NiFe-LDH catalysts. Such long-range gradient effects in nanoarray materials provide new opportunities to understand their boosted catalytic performances and to rationally design better catalytic materials. Graphical abstract: Image 1 Highlights: The highlights of our paper are: NiFe hydroxides with concentration and valence states gradient are prepared. Long-range asymmetrical structure is built based on NiFe hydroxides. Covalency of metal-oxygen bond is enhanced due to the electronic structure evolution. Electron and holes transfer are facilitated due to the gradient phenomenon.